An Interdisciplinary Approach for Compulsive Behavior in Dogs: A Case Report - d'Angelo, Danila; Sacchettino, Luigi; Carpentieri, Rosanna; Avallone, Luigi; Gatta, Claudia; Napolitano, Francesco (Frontiers in Veterinary Science, 2022)
Compulsive disorder is a debilitating condition affecting both humans and animals, characterized by intrusive thoughts and recurring out of place behaviors. Among them, tail chasing might represent one of the most common traits in compulsive dogs. Herein, we reported the case of a 7-year-old intact male German Shepherd mixed-breed dog, presenting with tail chasing behavior. He underwent a first behavioral evaluation one year before (at the age of six), when he injured himself with severe wounds at level of the tail and left thigh. To avoid any specific suffering and increase his physical health, of course, the study was carried out through an interdisciplinary approach, employing a veterinary behaviorist and rehabilitating dog instructor. Three months after pharmacological treatment with fluoxetine and alpha-s1casozepine, associated to a behavioral recovery program, the owner reported an improvement of compulsive events in his dog, in terms of intensity and frequency. Interestingly, over the following three months the dog did not experience any new tail chasing episodes.